The Effect of Competence and Internal Control System on Village Government Accountability with Organizational Commitment as Moderating Variable - Mustofa, Ardyan Firdausi; Muntiah, Nur Sayidatul; Susanti, Fitria Dwi (IAIN Surakarta, 2021)
This study explored the effect of competence and the internal control system on the accountability of the village government in Babadan District, Ponorogo Regency. It also seeks to determine whether organizational commitment as a moderating variable can weaken or strengthen the relationship between the independent variables and the dependent variable.. The population of this study is all village officials in the Babadan District, Ponorogo Regency. 100 samples were selected using Proportionate Random Sampling. Primary was obtained utilizing a questionnaire, which was distributed to 12 villages in Babadan District. The results of the multiple linear regression analysis employing SPSS version 26 indicate some important findings. First, competence and the internal control system as independent variables, and organizational commitment as moderating variables have a positive and significant effect on village government accountability. Second, organizational commitment cannot moderate the relationship between competence and village government accountability. Third, organizational commitment moderates the relationship between the internal control system and village government accountability and strengthen the relationship between the independent variables and the dependent variable.